Trypanosomes as a magnifying glass for cell and molecular biology - Lukeš, Julius; Speijer, Dave; Zíková, Alena; Alfonzo, Juan D; Hashimi, Hassan; Field, Mark C (Trends in parasitology, 2023)
The African trypanosome, Trypanosoma brucei, has developed into a flexible and robust experimental model for molecular and cellular parasitology, allowing us to better combat these and related parasites that cause worldwide suffering. Diminishing case numbers, due to efficient public health efforts, and recent development of new drug treatments have reduced the need for continued study of T. brucei in a disease context. However, we argue that this pathogen has been instrumental in revolutionary discoveries that have widely informed molecular and cellular biology and justifies continuing research as an experimental model. Ongoing work continues to contribute towards greater understanding of both diversified and conserved biological features. We discuss multiple examples where trypanosomes pushed the boundaries of cell biology and hope to inspire researchers to continue exploring these remarkable protists as tools for magnifying the inner workings of cells.
Keywords: genetic code; alternative oxidase; tRNA import; RNA editing; glycosome; endocytosis; Molecular Biology; Trypanosoma; molekulární biologie; Trypanosoma brucei brucei; GPI-anchor